UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI HIMPUNAN MENGGUNAKAN LKS DENGAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS VII SMP NEGERI 1 MARGAASIH - Gilang Hariawan Pratama; Asep Ikin Sugandi; Anik Yuliani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
As we know, there are still many students who still have difficulty understanding the set material. This of course affects the learning outcomes. Thereofere, a Problem Based Learning (PBL) learning method is needed into mathematics learning, with the hope that students are more familiar with and understand the concepts given to the set material. The purpose of this research is to improve the learning outcomes of mathematics on set material. This study uses a Class Action Research (CAR) model with 30 students in class VII-D SMPN 1 Margaasih. This research was conducted in three cycles, with each cycle consisting of: 1) Planning, 2) implementation, 3) observation, 4) reflection. The data analysis technique is to see the increase in learning outcomes from the three learning cycles with a limit of 85% reaching the KKM value of 75. The learning outcomes of SMP Negeri 1 Margaasih students who initially be concluded that with the Problem Based Learning (PBL) method students better understand the material and have an effect on increasing learning outcomes.